Asymptotic tests for general linear hypotheses on variance components in models of commutative quadratic type - Hartung, Joachim; Knapp, Guido (Universitätsbibliothek Dortmund, 1998)
In this paper we derive asymptotic x^2 -tests for general linear hypotheses on variance components using repeated variance components models. In two examples, the two-way nested classification model and the two-way crossed classification model with interaction, we explicitly investigate the properties of the asymptotic tests in small sample sizes.
Keywords: linear hypotheses on variance components; repeated variance components model; Wald- and likelihood ratio test statistic; 310